Comparison of Bacterial Diversity in Air and Water of a Major Urban Center - Dueker, M. Elias; French, Shaya; O’Mullan, Gregory D. (Frontiers in Microbiology, 2018)
The interaction of wind with aquatic and terrestrial surfaces is known to control the creation of microbial aerosols allowing for their entrainment into air masses that can be transported regionally and globally. Near surface interactions between urban waterways and urban air are understudied but some level of interaction among these bacterial communities would be expected and may be relevant to understanding both urban air and water quality. To address this gap related to patterns of local air-water microbial exchange, we utilized next-generation sequencing of 16S rRNA genes from paired air and water samples collected from 3 urban waterfront sites and evaluated their relative bacterial diversity. Aerosol samples at all sites were significantly more diverse than water samples. Only 17-22% of each site’s bacterial aerosol OTUs were present at every site. These shared aerosol OTUs included taxa associated with terrestrial systems (e.g. Bacillus), aquatic systems (e.g. Planktomarina) and sewage (e.g. Enterococcus). In fact, sewage-associated genera were detected in both aerosol and water samples, (e.g. Bifidobacterium, Blautia, Faecalibacterium), demonstrating the widespread influence of similar pollution sources across these urban environments. However, the majority (50-61%) of the aerosol OTUs at each site were unique to that site, suggesting that local sources are an important influence on bioaerosols. According to indicator species analysis, each site’s aerosols harbored the highest percentage of bacterial OTUs statistically determined to uniquely represent that site’s aquatic bacterial community, further demonstrating a local connection between water quality and air quality in the urban environment.